Психолого-педагогічні умови формування компетентності майбутнії фахівців під час навчання у вищому навчальному закладі - Бондаренко, Л. Ю.; Вершков, Олександр Олександрович; Bondarenko, L. Yu.; Вершков, Александр Александрович; Vershkov, Oleksandr (ТДАТУ, 2011)
Uk: Розкрито сутність понять «компетентнісний підхід». Ви-значено психолого-педагогічні умови розвитку особистості студента у ВНЗі. Розкрито критерії оцінки та етапи формування компетентності студентів. En: The essence of the concepts "competence approach" is revealed. The psychological and pedagogical conditions for the development of the personality of the student in the university have been determined. The evaluation criteria and stages of forming the competence of students are disclosed.
Psychological and pedagogical conditions for forming the competence of future specialists during their studies at a higher educational institution
Keywords: компетентність; психолого-педагогічні умови розвитку особистості; формування компетентності студента; образовательный процесс; специалист; соціалізація особистості; ключові компетентності; професійна компетентність; competence; psychological and pedagogical conditions of personality development; formation of student's competence; educational process; specialist